Reality of thermic tourism in Algeria - boulasbaa, mahmoude (Milev Journal of Research and Studies, 2016)
This Many countries realized the importance of thermic tourism, they worked to develop a set of its thermic sites, in addition to intertaing tourism services, exploiting areas of attraction which it has, and provided for that infrastructure, support services, and used a considerable potentialities of promotional methods and activities that attract an increasing number of internal and external tourists. On the basis of thermic tourism that is one of the tourism sector pillars and the most viable, and because of Algeria thermic headwaters which have healthy and therapeutic benefits, this paper has aimed to issue the reality of promotional activity for thermic tourism in Algeria, and the challenges faced to exploit the potentialities available for its development.